The Hermeneutics of Transmission: Deciphering Discourses on Poetry and the Arts in Early Modern Europe (1500-1800) - Blocker, Déborah (Intermédialités / Intermediality, 2005)
This article discusses how the constitution, circulation and institutionalization of discourses on poetry and the arts in early modern Europe could best be accounted for from a historical point of view. Pointing to various inconsistencies in the way historians of ideas have traditionally explained the rise of aesthetic discourses, the article examines the usefulness of the tools crafted by historians of the book for the development of such a project. Through an example, the drawbacks of interpretations based solely on serial bibliographies are also addressed, as the author argues for the importance of case studies, grounded in social, cultural and political history, through which various types of aesthetic practices may be made to appear. She also suggests that, to bypass the theoretical and practical deadlocks of traditional Begriffsgeschichte as far as the study of aesthetic practices is concerned, intellectual traditions and the actions that make them possible — that is “actions of transmission” — are to be promoted to the status of primary hermeneutic tools.